2018
DOI: 10.1152/ajplung.00373.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoke on pulmonary endothelial cells

Abstract: Cigarette smoking is the leading cause of preventable disease and death in the United States. Cardiovascular comorbidities associated with both active and secondhand cigarette smoking indicate the vascular toxicity of smoke exposure. Growing evidence supports the injurious effect of cigarette smoke on pulmonary endothelial cells and the roles of endothelial cell injury in development of acute respiratory distress syndrome (ARDS), emphysema, and pulmonary hypertension. This review summarizes results from studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 160 publications
(175 reference statements)
1
53
1
4
Order By: Relevance
“…Third, numerous studies of preclinical animal models and cultured cells have demonstrated that CS exposure increases pulmonary endothelial barrier permeability and pulmonary endothelial cell apoptosis. After CS-induced injury to endothelial cells, components of smoke enter the circulation via a more permeable endothelial barrier ( 13 ), subsequently leading to circulating endothelial cell injury. Thus the endothelial injury of the pulmonary vasculature might be more obvious than other circulating endothelial.…”
Section: Discussionmentioning
confidence: 99%
“…Third, numerous studies of preclinical animal models and cultured cells have demonstrated that CS exposure increases pulmonary endothelial barrier permeability and pulmonary endothelial cell apoptosis. After CS-induced injury to endothelial cells, components of smoke enter the circulation via a more permeable endothelial barrier ( 13 ), subsequently leading to circulating endothelial cell injury. Thus the endothelial injury of the pulmonary vasculature might be more obvious than other circulating endothelial.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic kidney diseases have increased levels of anti-endothelial cell antibodies, and decreased expression of both adherens and tight junction proteins VE-cadherin, claudin-1, and zonula occludens-1 [ 36 ]. Cigarette smoking disrupts intercellular adhesion molecules between ECs and induces their apoptosis [ 37 ]. In COPD patients, circulating anti-endothelial cell antibodies along with chronic oxidative and inflammatory stress induces apoptosis of ECs [ 38 ].…”
Section: Ed Associated To Aging and Chronic Diseasementioning
confidence: 99%
“…(47). Cigarette smoke exposures are known to disrupt alveolar-epithelial barrier integrity leading to increase proteins in bronchoalveolar lavage fluid and lung edema and an increase inflammation and hypoxemia (12,44,75) In humans, cigarette smoke has also been associated with increased susceptibility to acute respiratory distress syndrome and its severity, which is closely correlated with the level of smoking (36,44). Additionally, in a prospective study, the level of cotinine, a nicotine metabolite, measured on patients upon arrival, was closely correlated with the severity of trauma-induced ALI (13).…”
Section: Introductionmentioning
confidence: 99%